Hubungan Kemampuan Literasi Digital Guru dengan Learning Loss pada Siswa Sekolah Dasar di Nagari Lima Kaum - Safrizal, Safrizal; Yulnetri, Yulnetri; Wulandari, Nalfa (Jurnal Didaktika Pendidikan Dasar, 2023)
The aim of the research is to describe the relationship between teachers' digital literacy abilities and learning loss in elementary school students in Nagari Lima Kaum. The research method is a correlational quantitative method. The population is 83 teachers, while the sample is 64 teachers obtained through stratified random sampling technique. The data analysis technique used a simple linear regression test with the help of the SPSS 22 application. The results showed that there was a relationship between teachers' digital literacy skills and learning loss in elementary school students, with sig. 0.014 < 0.05, with the contribution of the teacher's digital literacy ability to reduce learning loss in elementary school students by 9.4%, and leads to the negative, meaning that the higher the teacher's digital literacy ability, the learning loss in students will decrease, conversely the lower the ability teacher's digital literacy, the learning loss in students will be higher. So it can be concluded that in this study H0 was rejected and H1 was accepted, so it can be concluded that there is a significant relationship between teachers' digital literacy skills and learning loss in elementary school students in Nagari Lima Kaum.